A novel adaptive order/parameter identification method for variable order systems application in viscoelastic soft tissue modeling. (September 2017) - Tabatabaei, S. Sepehr; Talebi, H.A.; Tavakoli, M.
Abstract: This paper presents an adaptive system identification approach to identify the order and parameters of a specific type of variable order systems, which, as a motivating example, describes the stress-strain relation of viscoelastic materials. First, the concept of non-integer order modeling will be introduced. Next, the proposed order/parameter identification approach will be presented. Afterwards, a simulation study is performed to validate the identification approach. Finally, the method will be applied on real data gathered from an experimental study for further validation.